Sportpreneurship: A Sports-Based Business Development Strategy for Millennials - Bujang; Haqiyah, Aridhotul; Abidin, Dindin; Basri, Hasan; Kusumawati, Mia; Ridlo, Azi Faiz; Ekowati; Arisman (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
Sportpreneurship, or sports-based entrepreneurship, is becoming an important phenomenon in the modern business world, especially among millennials who have a high tendency towards innovation and technology. The millennial generation is faced with a great opportunity to take advantage of sports as a rapidly growing business sector. This study aims to analyze sports-based business development strategies that are relevant to the millennial generation. Using a qualitative approach, this research identifies the opportunities, challenges, and potentials that exist in the development of sportpreneurship. The results of the study show that interest in digital sports, the development of fitness applications, and social media as marketing platforms, are important aspects of the millennial sports business model. This research provides practical recommendations for the millennial generation to explore the growing market and utilize technology in optimizing the potential of the sports business.